Comparison of coded‐wire tagging with parentage‐based tagging and genetic stock identification in a large‐scale coho salmon fisheries application in British Columbia, Canada. (11th October 2018) - Beacham, Terry D.; Wallace, Colin; Jonsen, Kim; McIntosh, Brenda; Candy, John R.; Willis, David; Lynch, Cheryl; Moore, Jean‐Sébastien; Bernatchez, Louis; Withler, Ruth E.
Abstract: Wild Pacific salmon, including Coho salmon Onchorynchus kisutch, have been supplemented with hatchery propagation for over 50 years in support of increased ocean harvest and conservation of threatened populations. In Canada, the Wild Salmon Policy for Pacific salmon was established with the goal of maintaining and restoring healthy and diverse Pacific salmon populations, making conservation of wild salmon and their habitats the highest priority for resource management decision‐making. A new approach to the assessment and management of wild coho salmon, and the associated hatchery production and fishery management is needed. Implementation of parentage‐based tagging (PBT) may overcome problems associated with coded‐wire tag‐based (CWT) assessment and management of coho salmon fisheries, providing at a minimum information equivalent to that derived from the CWT program. PBT and genetic stock identification (GSI) were used to identify coho salmon sampled in fisheries (8, 006 individuals) and escapements (1, 692 individuals) in British Columbia to specific conservation units (CU), populations, and broodyears. Individuals were genotyped at 304 single nucleotide polymorphisms (SNPs) via direct sequencing of amplicons. Very high accuracy of assignment to population (100%) via PBT for 543 jack (age 2) assigned to correct age and collection location and 265 coded‐wire tag (CWT, age 3) coho salmon assigned to correct age and release location was observed, with a 40, 774—individual, 267—population baseline available for assignment. Coho salmon from un‐CWTed enhanced populations contributed 65% of the catch in southern recreational fisheries in 2017. Application of a PBT‐GSI system of identification to individuals in 2017 fisheries and escapements provided high‐resolution estimates of stock composition, catch, and exploitation rate by CU or population, providing an alternate and more effective method in the assessment and management of Canadian‐origin coho salmon relative to CWTs, and an opportunity for a genetic‐based system to replace the current CWT system for coho salmon assessment.